2022
DOI: 10.3390/ijms24010646
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Is an Important Mediator in the Final Common Pathway of Chronic Kidney Disease to End-Stage Renal Disease

Abstract: Chronic kidney disease (CKD) is a slow-developing, progressive deterioration of renal function. The final common pathway in the pathophysiology of CKD involves glomerular sclerosis, tubular atrophy and interstitial fibrosis. Transforming growth factor-beta (TGF-β) stimulates the differentiation of fibroblasts towards myofibroblasts and the production of extracellular matrix (ECM) molecules, and thereby interstitial fibrosis. It has been shown that endoglin (ENG, CD105), primarily expressed in endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Nephrotoxicants constitute a significant etiological factor contributing to the occurrence of AKI. Clinical studies have identified various agents, including cisplatin, gentamicin, glycerol, radiocontrast agents, and heavy metal ions such as mercury, as known nephrotoxic substances (1).…”
Section: Aki Induced By Nephrotoxicantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nephrotoxicants constitute a significant etiological factor contributing to the occurrence of AKI. Clinical studies have identified various agents, including cisplatin, gentamicin, glycerol, radiocontrast agents, and heavy metal ions such as mercury, as known nephrotoxic substances (1).…”
Section: Aki Induced By Nephrotoxicantsmentioning
confidence: 99%
“…For instance, certain herbs possessing antioxidant, vasodilatory, and diuretic properties have demonstrated nephroprotective effects in cases of glycerol-induced AKI. Moreover, herbs with antimicrobial and anti-inflammatory properties can be employed in the management of sepsis-associated AKI (1,(11)(12)(13)(14).…”
Section: Aki Induced By Sepsismentioning
confidence: 99%
See 3 more Smart Citations